Kekuatan Hukum Kedudukan Kepala Desa Menerbitkan Surat Keterangan Tanah Ditinjau Dari Peraturan Pemerintah Nomor 18 Tahun 2021 Tentang Pendaftaran Tanah - Soputan, Mien; Wongkar, Vonny Anneke; Sumakul, Tommy Ferdy (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The legal force of the Village Head in the land certificate (SKT) reviewed from Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration (PPPT 2021) as a replacement for Government Regulation number 24 of 1997 concerning Land Registration (PPPT 1997) is interesting to study, especially in rural areas. This study uses the normative research method with three approaches: 1. regulatory approach (village government law), 2. conceptual approach (preventing abuse of the position of the Village Head) 3. analysis approach of conformity with legislation. The birth of PPPT 2021 concerning land registration as a replacement for PPPT 1997 regulates the transfer of land rights before the PPAT while SKT has become the basis for villagers to transfer land rights or buy and sell their land only before the Village Head, until this causes disputes.